2005
DOI: 10.1007/s10733-005-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Transformations in Low-Temperature Matrices Containing Radical Cations of Organotin Compounds

Abstract: Charge transfer to matrix molecules was found to be the principal photochemical reaction of the radical cations Me 4 and Me 6 . It was shown that the difference in the localization of positive charge in the ground state of these radical cations (at the Sn-C bond in Me 4 and at the Sn-Sn bond in Me 6 ) did not affect the pathways of their photochemical reactions. Sn +. Sn 2 +. Sn +. Sn 2 +.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The analysis of this electron density shows that the removal of one electron from the outermost t 2 molecular orbital of TMSn is accompanied by a localization of this MO between these two moieties. This confirms also the assumptions of Belokon et al26, who showed that the positive charge is localized on the SnC bond. The analysis of the electronic density difference between the neutral and ionic species reveals that the electronic density in CH 3 is reduced in the complex.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The analysis of this electron density shows that the removal of one electron from the outermost t 2 molecular orbital of TMSn is accompanied by a localization of this MO between these two moieties. This confirms also the assumptions of Belokon et al26, who showed that the positive charge is localized on the SnC bond. The analysis of the electronic density difference between the neutral and ionic species reveals that the electronic density in CH 3 is reduced in the complex.…”
Section: Resultssupporting
confidence: 91%
“…To the best of our knowledge, no definite statement is available in the literature. More recently, Belokon et al26 showed that the photochemical reactions of SnMe 4+ ions trapped in cooled matrices occur through charge transfer to the neighboring molecules. Finally, experimental evidence was given for the formation of the TMSn + cation in single‐electron capture reactions between OH + and TMSn27.…”
Section: Introductionmentioning
confidence: 99%